Retrospective study on prediction of mortality outcome Using post cardiac surgery prognostic scale (pocas) Among patient underwent cardiac surgery at Hospital Universiti Sains Malaysia Kelantan - Arshad, Ahmad Wafi Mohd (2020)
Background: Demand for cardiothoracic surgery is increasing in recent decades from better health service improvement throughout the world resulting in higher life expectancies and better health care coverage. We study association between outcome of 90 days mortality post cardiac surgery in Cardiothoracic Unit, HUSM and prognostic scale; Post- operative Cardiac Surgery Score (POCAS) and EuroSCORE II in order to improve post-operative care of cardiac surgery patient in our center. Methods: This is a retrospective record review study of adult patient who underwent cardiac surgery in Cardiothoracic Unit, Hospital Universiti Sains Malaysia, Kelantan from 1st January 2012 until 31st December 2018. Data was collected from medical records and post-operation registration database. Cardiac surgery included are isolated coronary artery bypass surgery (CABG), valve replacement or repair surgery, combined operation of CABG and valve surgery and congenital heart septal closure surgery. Results: A total of 158 patients who underwent cardiac surgery were included in this study. We found 133 survivors and 25 cases of mortality within 90 days after cardiac surgery throughout the period of study. Based on POCAS score, we found there is association of this scale with mortality cases. By regression analysis, we found that when there is an increase of 1 score of POCAS, there is 1.286 times increment of odds for 90 days post-operative mortality (AOR; 1.286, 95% CI; 1.172 – 1.410, p =<0.001). Furthermore, we study on regression analysis and found there is significant association as well between mortality cases with EuroSCORE II scale. When adjusted for 90 days post-operative mortality, we found that with an increase of 1 score of EuroSCORE II scale, patient has 2.875 times the odds to have mortality 90 days post cardiac surgery in HUSM population (AOR 2.875, 95% CI; 1.923 – 4.298, p =<0.001). Conclusion: There is significant association between POCAS score which is post-operative biochemical and hemodynamics parameters scale with 90 days post-operative mortality. There is significant association between mortality prediction of EuroSCORE II and mortality observed cases as well. Prediction of mortality after cardiac surgery may enlighten clinicians to lay down strategy of intensive care in complex cardiac surgery cases.